Paredes de contenção autoportantes em solos argilosos sobreconsolidados: Análise considerando os efeitos da consolidação - Paulo Sousa (2010)
The behaviour of a cantilever wall in an overconsolidated clay is simulated during and after theconstruction period by a computer program based on the finite element method. The programincorporates the Biot consolidation theory (coupled formulation of the flow and equilibriumequations) with constitutive relations simulated by the p-q- critical state model. Specialemphasis is given to the analysis, during and after the construction period, of the excess porepressures, shear stresses, stress levels and displacements in the ground, as well as bendingmoments, displacements and pressures on the wall.